The effects of a transdiagnostic prevention programme for behavioural and emotional difficulties, self-esteem and prosocial behaviour among primary school children in Malaysia: a preliminary study - Chai, Carmen Wan Yin; Chen, Serena Sin Loke; Thong, Koon Nam (2019)
The objectives of the present study are to examine the effects of a transdiagnostic prevention programme on Malaysian children’s behavioural and emotional difficulties, self-esteem, and prosocial behaviour. A total of 18 primary school children, aged between 10 to 12 years old were recruited through purposive sampling at Kampar into this study. All the children were given questionnaires to measure emotional symptoms, conduct problems, hyperactivity-inattention, peer problems, total difficulties, self-esteem, and prosocial behaviour before and after participating in the 2 days programme, and during the 6-weeks follow-up assessment. The results of the study indicated significant decrements in conduct problems and total difficulties at posttest, followed by significant decrements in hyperactivity-inattention and peer problems at followup assessment. Self-esteem also reported a significant increment at follow-up assessment, but there are no significant differences found for emotional symptoms and prosocial behaviour. The study findings provided preliminary empirical support on the effectiveness of transdiagnostic prevention programme on Malaysian school-age children, as well as several other practical implications.